Techniques of Humor in Das’ad Latif Preaching - Inda Nur Abida, Fithriyah; Budi Darma, Diana (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
Humor serves primarily as a vehicle to convey religious teachings and therefore humor has become an inseparable part of religious practices in Indonesia. The relation between humor and religion holds particularly vital instrument to bridge communication and understanding between diverse religious groups including fundamentalists. In the Muslim community, humor prominently found in preachers, recitations, and other religious activities. The tradition of Islamic preaching in Indonesia cannot be separated from humor. The preaching task invites and even demands the use of humor. One of the famous Da’i who use humor in his preaching is Ustadz Das’ad Latif. This paper analyses the techniques used in Das’ad Latif preaching. The method used in this paper is descriptive method with a qualitative approach. The most widely used humor technique dimension is language followed by the second most widely used dimension is logic. The third dimension is action and the last is identity. This is because verbal strength, where the language category is humor that is conveyed verbally, can represent other categories such as logic (humor that comes from ideas or thoughts), action (humor that comes from non-verbal communication), identity (humor that comes from one's identity or existence)